PENGGUNAAN PENDEKATAN SOSIOSAINTIFIK DALAM PENGEMBANGAN DAN IMPLEMENTASI RANCANGAN TUGAS TEMATIK BANJIR PADA SISWA SMP NEGERI 3 TAHUNA - Jeane V. Tumangkeng (Charm Sains: Jurnal Pendidikan Fisika, 2022)
The socioscientific approach is a learning approach that is oriented to the context of science and its relationship to social life in society. Thematic learning about flooding is learning that uses themes in linking several subjects so that it is more effective and meaningful because it provides real experiences for students. The objectives of this study are (1) to develop instructional designs on thematic tasks with teachers and parents or the community as learning materials for students, (2) describe the process of implementing flood thematic tasks, (3) describe students' perceptions of material design and implementation of flood thematic learning, (4) improve the mastery of physics concepts, the relationship of mastery of physics concepts with context, the relationship of mastery of physics concepts with biology and mathematics in learning flood thematic tasks with a socio-scientific approach. This study was designed for students of SMP Negeri 3 Tahuna grade VIIIA. Data analysis methods include quantitative analysis used to describe indicators on research variables, indicator correlation using Spearman level correlation, indicator changes from the initial meeting to the final meeting and qualitative analysis used to describe student attitudes and perceptions of learning design and implementation activities. The results of this study obtained that students were actively involved in the discussion of concepts and their application as well as in observation activities. The achievement of group activities between the concept of physics and the context has a perfect correlation